Fighting Incivility in the Workplace for Women and for All Workers: The Challenge of Primary Prevention - Di Fabio, Annamaria; Duradoni, Mirko (Frontiers in Psychology, 2019)
This article discusses the role of several constructs, such as workplace relational civility (WRC), positive relational management (PRM), and emotional intelligence (EI), as possible primary preventive resources to effectively deal with interpersonal mistreatment in the workplace (i.e., incivility). Since women endure workplace incivility more frequently than men, their well-being is particularly at risk. Thus, the possibilities for further research and primary prevention interventions in line with the achievement of the fifth Sustainable Development Goal (SDG 5) are discussed.